El contexto del desarrollo - Cock, James H. (International Center for Tropical Agriculture, 1991)
Development models are outlined to shed light on cassava's potential to generate economic growth. Since small cassava producers are to a large extent marginalized from the development process in Latin America, the CIAT cassava program has tried to define development strategies that are clearly oriented toward the poorer segments of the rural population, while contributing whenever possible to increasing urban welfare as well. This strategy is based on integrated production, processing, and marketing projects. The execution of these projects follows a series of stages: macroeconomic analysis, pilot project site selection, pilot plant implementation, and project expansion. This strategy has been successfully implemented on the north coast of Colombia, where marketing was identified as a major constraint of small cassava producers. An expansive alternative market was opened: the animal feed market. The industry was established on the basis of small-producer associations; when local fresh market price was high, these associations could sell into that market, and when prices dropped, they had the alternative of drying the cassava. Forty plants now operate on the north coast and are bringing benefits in terms of increased income, employment, and a new community spirit. (CIAT)